KARAKTERISTIK PELAYANAN MIKROLET 09A (TANAH ABANG – KEBAYORAN LAMA) - Maula, Raudhatul; Situmorang, Rahel; Suharto, Benny Benyamin (Universitas Trisakti, 2023)
The 2015 Jabodetabek Transportation Master Plan indicates that Mikrolet are not included in the planned public transport. Tanah Abang - Kebayoran Lama route is a busy route with community activities because it passes through many city activity centers (trade, housing, as well as public and social services). This study examines the needs of the community regarding Mikrolet public transportation services in accordance with the characteristics of microbus services 09A. This research method is carried out by processing the data obtained from the questionnaire and presenting it descriptively, then the results are compared with the service characteristics of other public transportation modes. The results of this study, Mikrolet has characteristics that other modes of public transportation do not have, namely waiting time, affordability of fares, and flexibility of movement.